Kajian Penggunaan Batu Gunung Barani Untuk Bahan Campuran AC-BC - Ivon Tambing; Alpius; Louise Elizabeth Radjawane (Paulus Civil Engineering Journal, 2021)
This study aims to determine the characteristics of the Mount Barani rock, determine the composition of the AC-BC mixture and the remaining Marshall Stability in the AC-BC mixture by referring to the 2018 General Specifications. The results of this study indicate that the characteristics of the aggregates originating from Mount Barani, Manggau Village, have met specifications according to the 2018 Bina Marga Standard with a coarse aggregate composition design of 42.82%, 45.73% fine aggregate, 5.45% filler, and the optimum asphalt content is 6.00%. After doing the Conventional Marshall test, the characteristics of the asphalt mixture were obtained that had met all the standard specifications. Marshall Immersion (Marshall Stability Remaining) in the AC-BC mixture using the aggregate from Mount Barani, Manggau Village, meets the General Bina Marga 2018 standard / specification, which is at least 90%.